2020
DOI: 10.1002/ange.202008358
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Dearomatization of Naphthalene Derivatives by Photoredox‐Catalyzed 1,2‐Hydroalkylation

Abstract: An intermolecular hydroalkylative dearomatization of naphthalenes with commercially available α‐amino acids is achieved via visible‐light photoredox catalysis. With an organic photocatalyst, a series of multi‐substituted 1,2‐dihydronaphthalenes are obtained in good‐to‐excellent yields. Intriguingly, by tuning the substituents at the C2 position of naphthalenes, formal dearomative [3+2] cycloadditions occur exclusively via a hydroalkylative dearomatization–cyclization sequence. This overall redox‐neutral method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 107 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…So, the excited state photocatalyst can oxidize both NH 4 SCN and 1 a , furthermore, the fluorescence quenching experiment revealed that the SET process was feasible between 1 a and the excited state photocatalyst (Figure 2). Initially, under blue light irradiation, 4CzIPN transformed to 4CzIPN*, which subsequently oxidized 1 a to its corresponding radical cation 1a+ ${{1\hskip0.17em{\bf a}}^{\bullet +}}$ [34c] and furnishing photocatalyst radical anion 4CzIPN- ${{4{\rm C}{\rm z}{\rm I}{\rm P}{\rm N}}^{\bullet -}}$ . Next, the radical cation of 1 a combined with thiocyanate anion and produced vinyl radical A , which subsequently experiences an intramolecular 6‐exo‐trig cyclization, creating the spiro radical B .…”
Section: Resultsmentioning
confidence: 99%
“…So, the excited state photocatalyst can oxidize both NH 4 SCN and 1 a , furthermore, the fluorescence quenching experiment revealed that the SET process was feasible between 1 a and the excited state photocatalyst (Figure 2). Initially, under blue light irradiation, 4CzIPN transformed to 4CzIPN*, which subsequently oxidized 1 a to its corresponding radical cation 1a+ ${{1\hskip0.17em{\bf a}}^{\bullet +}}$ [34c] and furnishing photocatalyst radical anion 4CzIPN- ${{4{\rm C}{\rm z}{\rm I}{\rm P}{\rm N}}^{\bullet -}}$ . Next, the radical cation of 1 a combined with thiocyanate anion and produced vinyl radical A , which subsequently experiences an intramolecular 6‐exo‐trig cyclization, creating the spiro radical B .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, visible-light photoredox catalysis [36][37][38][39][40][41][42][43][44][45] has emerged as a promising strategy for developing mild protocols for dearomatization, [46][47][48][49][50][51][52][53][54][55][56][57][58][59] including several significant protocols for the dearomatization of nonactivated arenes, [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] such as dearomative cycloadditions that were mainly from the groups of Sarlah and Bach, [60][61][62][63] and oxidative dearomatization. [64][65][66] A distinct redox-neutral hydroalkylative dearomatization of naphthalene derivatives was also reported by the group of Zhang, Mei and You.…”
Section: Introductionmentioning
confidence: 99%
“…[64][65][66] A distinct redox-neutral hydroalkylative dearomatization of naphthalene derivatives was also reported by the group of Zhang, Mei and You. 67 However, there are only a handful of reports on visible-light-induced reductive dearomatization of non-activated arenes. [68][69][70][71][72][73][74] Of particular note, the groups of König 68 and Miyake 69 independently reported the challenging photoredox catalyst (PC) induced Birch-type reduction of arenes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, visible-light photoredox catalysis [35][36][37][38][39][40][41][42][43][44] has emerged as a promising strategy for developing mild protocols for dearomatization, [45][46][47][48][49][50][51][52][53][54][55][56][57][58] including several significant protocols for the dearomatization of nonactivated arenes, [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] such as dearomative cycloadditions mainly from the groups of Sarlah and Bach, [59][60][61][62] and oxidative dearomatization. [63][64][65] A distinct redox-neutral hydroalkylative dearomatization of naphthalene derivatives was also reported by the group of Zhang, Mei and You.…”
Section: Introductionmentioning
confidence: 99%
“…[63][64][65] A distinct redox-neutral hydroalkylative dearomatization of naphthalene derivatives was also reported by the group of Zhang, Mei and You. 66 However, there are only a handful of reports on visible-light-induced reductive dearomatization of non-activated arenes. [67][68][69][70][71][72][73] Of particular note, the groups of König 67 and Miyake 68 independently reported the challenging photoredox catalyst (PC) promoted Birch-type reduction of arenes.…”
Section: Introductionmentioning
confidence: 99%